Mindfulness pada Komunikasi Antarbudaya: Komunikasi Komunitas Virtual pada Akun Instagram @merawatpapua dalam Merespons Stereotip - Rusyda Fauzana (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Intercultural communication on social media opens up opportunities to understand other cultural groups. Currently, communications of virtual community in digital public spaces are widely carried out for various purposes, one of which is to explore information and build relationships. Sometimes stereotypes arise in relationships and disrupt the communication process. The purpose of this study is to explore how the mindfulness on intercultural communication of a virtual community responds to stereotypes about Papuans in the uploads of the @merawatpapua account. This study uses a qualitative approach using virtual ethnography methods. Data collection was carried out by engaging in active discussions and observations on the @merawatpapua account. Data analysis used the Mindfulness concept initiated by Ellen Langer. The results of the study show that the virtual community in the @merawatpapua account has the characteristics of mindfulness in responding to stereotypes about Papua. The stages carried out are by creating new categories of information, being open to new information, and being aware of the many differences in perspective